PENGARUH KINERJA KEUANGAN, KEPEMILIKAN INSTITUSIONAL, UKURAN DEWAN PENGAWAS SYARIAH, LEVERAGE TERHADAP PENGUNGKAPAN ISLAMIC SOCIAL REPORTING PADA PERBANKAN SYARIAH DI INDONESIA (Studi pada Perbankan Syariah Tahun 2013-2015) - Firdaus, Indra; Darlis, Edfan; Indrawati, Novita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The purpose of this study was to analyze the effect of finance perfomance, institusional ownership, sharia supervisory board size, leverage toward islamic social reporting disclosure in indonesian sharia bank. The sample was selected using purposive sampling method and obtained 33 Observations. Data were collected from sharia bank in Indonesian in 2013-2015. Data were analyzed usin, Multiple Linear Regression (SPSS Versi 17). The result showed partial finance performance, institusional ownership, sharia supervisory board size did not affect the disclosure of Islamic social reporting, while the leverage variable affect the disclosure of Islamic social reporting.Keyword : Finance Performance, Ownership Institusional, Sharia Supervisory Board Size, Leverage, Islamic Social Reporting Disclosure.